Usefulness and Prospects of Sentinel Lymph Node Biopsy for Patients With Breast Cancer Using the Medical Imaging Projection System - Nakamura, Yuki; Takada, Masahiro; Imamura, Michiko; Higami, Akane; Jiaxi, He; Fujino, Makoto; Nakagawa, Rie; Inagaki, Yukiko; Matsumoto, Yoshiaki; Kawaguchi, Kosuke; Kawashima, Masahiro; Suzuki, Eiji; et al. (Frontiers in Oncology, 2021)
Background: The Medical Imaging Projection System (MIPS) projects indocyanine green (ICG) fluorescence images directly on the surgical field using a projection mapping technique. We conducted an observational study of sentinel lymph node (SLN) biopsy using the prototype MIPS; we found a high identification rate. However, the number of SLN-positive cases was small, and the sensitivity could not be evaluated. The aim of this study was to investigate the clinical usefulness of the MIPS assisted ICG fluorescence method using commercially available equipment. Methods: This was a retrospective observational study. Patients with primary breast cancer who underwent SLN biopsy using the MIPS at Kyoto University Hospital from April to December 2020 were included in the study. The primary endpoints were the identification rate of SLNs and detection of positive SLNs by the MIPS. The secondary endpoint was the number of SLNs excised using the MIPS per patient. We also conducted a questionnaire survey focused on the utility of the MIPS; it involved doctors with an experience in using the MIPS. Results: Seventy-nine patients (84 procedures) were included in the study. In 60 (71%) procedures, both the radioisotope (RI) method and MIPS were used. At least one SLN could be detected by the MIPS in all the procedures, with an identification rate of 100% (95% confidence interval 95.6–100%). A total of 19 (7%) positive SLNs were removed, which were identifiable by the MIPS. Among 57 patients in whom the MIPS and RI methods were used, there was no positive SLN only identified by the RI method. The results of the questionnaire survey showed that the MIPS enabled the operator and assistant to share the ICG fluorescence image in the surgical field and to communicate with each other easily. Conclusion: The current study demonstrated that the identification rate of SLNs using the MIPS was high, and the MIPS can be used for detecting positive SLNs. It was suggested that the MIPS will be useful in learning SLN biopsy procedures.